Terpasung Dalam Bualan Kepentingan - Zalukhu, Bintang; Wirahyuda, Fauzi; Sazali, Hasan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine the representation of female beauty in Garnier Sakura White advertisements. This type of research uses a qualitative descriptive research approach. Data obtained from garnier sakura white advertising posters. This research was conducted using the semiotic analysis method of Charles Sanders Peirce and also Marxist analysis. The results of this study show that the advertisement implies that the beautiful label of a woman is just a trick that ends up only for the benefit of certain parties in making coffers of money. As a result, many societies, especially women, are shackled in boasting interests that are only for certain parties to enjoy. It is as if the standard of human living, including the beauty of women is also measured according to the advertisements that are aired. Keywords: Beauty, Advertising, Semiotics, and Marxist.